Method of analysis of dimensions of physical quantities - Mukushev, B.A.; Sydykova, J.K.; Yerzhenbek, B.; Bitibaeva, J.M.; Bateshov, E.A.; Khuanbay, E.; Zhukenov, M.K.; Zheldybaeva, B.S. (Recent Contributions to Physics, 2023)
At the initial stage of physical research, a number of qualitative methods are used to create simple models reflecting the main parameters of the physical processes under consideration. One of the important qualitative methods of physical research is the method of analyzing the dimensions of physical quantities. The application of this scientific method makes it possible to estimate approximately the final results of the study of physical phenomena and objects. The article discusses the ways of using the dimension method in physical research. The conditions for the application of this method in modeling and analyzing physical phenomena and objects are established: functional dependencies between different physical quantities must be power-law; the rule N-K=1 must be fulfilled. The limitations necessary for the analysis of physical processes by the method of dimensions are shown. The methodological function of the analysis of dimensions of physical quantities is studied and the effectiveness of this method in processing experimental results is revealed. An example is presented in which the "apparent" dependence of physical quantities on other quantities is rejected. The phenomenon of propagation of a spherical shock wave of a point explosion, which is of great importance in the study of nuclear explosions, has been studied on the basis of this method. The role and place of the analysis of dimensions of physical quantities in comparison of theoretical and experimental results are determined.